2019
DOI: 10.1101/764647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide changes in genetic diversity in a population ofMyotis lucifugusaffected by white-nose syndrome

Abstract: ABSTRACTNovel pathogens can cause massive declines in populations, and even extirpation of hosts. But disease can also act as a selective pressure on survivors, driving the evolution of resistance or tolerance. Bat white-nose syndrome (WNS) is a rapidly spreading wildlife disease in North America. The fungus causing the disease invades skin tissues of hibernating bats, resulting in disruption of hibernation behavior, premature energy depletion, and subsequent death. We used who… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…Three studies reported evidence of genetic changes between declining and persisting M. lucifugus 136,146,147 . However, another study 148 found no such differences in M. lucifugus populations before and after WNS-induced declines but did find increased differentiation between bat populations in NY and Pennsylvania after WNS declines. Differences among these studies may be due to differences in sampling design and methodology or could reflect biological differences in selection among populations.…”
Section: Host Persistencementioning
confidence: 88%
“…Three studies reported evidence of genetic changes between declining and persisting M. lucifugus 136,146,147 . However, another study 148 found no such differences in M. lucifugus populations before and after WNS-induced declines but did find increased differentiation between bat populations in NY and Pennsylvania after WNS declines. Differences among these studies may be due to differences in sampling design and methodology or could reflect biological differences in selection among populations.…”
Section: Host Persistencementioning
confidence: 88%
“…Such effective adaptive immunity may take more generations to establish in naturally evolving populations, consistent with the undetectable WNS selection on the DRB gene and presumably also other MHC genes in current bat populations. A recent study using whole‐genome sequencing data from little brown bats detected signals of WNS selection on only one immune gene, MASP1, while all the other candidate genes were involved in hibernation behavior or fat storage (Gignoux‐Wolfsohn et al., 2018), further supporting the lack of WNS selection on MHC genes and the function of alternative survival mechanisms (Lilley et al., 2020).…”
Section: Discussionmentioning
confidence: 93%
“…For highly variable loci like the MHC gene, bottlenecks might have little impact on heterozygosity, but genetic drift during the decline of population size can cause substantial losses of rare alleles and allelic richness (Eimes et al., 2011; Sutton et al., 2015). In fact, demographic bottlenecks were observed in PA sites during sampling given the high rate of WNS‐related mortality and rarity of surviving bats (but see Lilley et al., 2020). Individuals from VT were proposed to have similar MHC allelic diversity as the nearby NY individuals based on high levels of regional gene flow (Vonhof et al., 2015); however, our data showed relatively lower allelic richness and a weak genetic distinction of the VT samples, similar to the lowest post‐WNS allele frequencies among VT individuals detected in another study (Gignoux‐Wolfsohn et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the population level, rapid evolution in response to disease can be detected by tracking changes in allele frequency before, during, and after the outbreak of disease (14,15). However, such analyses are resource-intensive and therefore still challenging in wildlife systems (but see 16,17,18). Reduced representation techniques such as restriction-site associated DNA-sequencing (RADseq) (19) have made the acquisition of genome-wide, timeseries genetic data more accessible in non-model systems (20).…”
Section: Introductionmentioning
confidence: 99%